Highly cultural significant edible and toxic mushrooms among the Tseltal from the Highlands of Chiapas, Mexico - Ruan-Soto, Felipe (Ethnobiology and Conservation, 2020)
The concept of cultural significance and its quantitative evaluation are useful to recognize which species (both edible and toxic) are the most relevant within a specific community. This work lists the most culturally significant edible and toxic species for the Tseltal groups in the Highlands of Chiapas. It also evaluates whether the composition and significance of these is different between the different Tseltal communities, proving the hypothesis that the edible and toxic species are not the same nor do they have the same level of significance in different settlements. One hundred and ninety-three interviews were carried out with Tseltal participants regarding edible and toxic mushrooms. The information was analyzed both qualitatively and quantitatively, using multivariate methods. People recognized 25 edible taxa whose names differ across the seven communities. The most frequently mentioned and consumed taxa are Amanita complex. caesarea, Cantharellus complex. cibarius and Agaricus spp. The classification analysis based on the relative frequency of mention for edible species, shows a variation pattern explained by the geographic, cultural and linguistic variation between Tseltal groups. For toxic mushrooms, people recognized and assigned names to 17 taxa. Only 17% of the interviewees assign at least one name to these species. The results show that Tseltal peoples from the Highlands of Chiapas are highly mycophilic. Furthermore, clear differences within the seven Tseltal groups are clear, not only with regards to lexical variations, but also regarding the number of known species, the species that are known and their degree of significance.